1999
DOI: 10.1093/brain/122.9.1651
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing in Parkinson's and Huntington's disease

Abstract: There is conjoining experimental and clinical evidence supporting a fundamental role of the basal ganglia as a sensory analyser engaged in central somatosensory control. This study was aimed at investigating the functional anatomy of sensory processing in two clinical conditions characterized by basal ganglia dysfunction, i.e. Parkinson's and Huntington's disease. Based on previously recorded data of somatosensory evoked potentials, we expected deficient sensory-evoked activation in cortical areas that receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
132
2
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(147 citation statements)
references
References 68 publications
10
132
2
3
Order By: Relevance
“…HD patients can show abnormal somatosensory processing (Abbruzzese, Dall'Agata, Morena, Reni, & Favale, 1990;Boecker et al, 1999;Kuwert et al, 1993;Topper, Schwarz, Podoll, Domges, & Noth, 1993). However, in patients with somatosensory deafferentation, impaired proprioception can actually facilitate mirror-inverted movements (Lajoie et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…HD patients can show abnormal somatosensory processing (Abbruzzese, Dall'Agata, Morena, Reni, & Favale, 1990;Boecker et al, 1999;Kuwert et al, 1993;Topper, Schwarz, Podoll, Domges, & Noth, 1993). However, in patients with somatosensory deafferentation, impaired proprioception can actually facilitate mirror-inverted movements (Lajoie et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a reduced efficiency of sensorimotor processing may induce an increased force specification. Disturbed sensorimotor activity in HD has been suggested because of a total suppression or reduced activity of the reactive EMG response (Fellows et al 1997;Noth et al 1985), an abnormal (sub)cortical activation during passive sensory stimulation (Boecker et al 1999), changes in somatosensory evoked potentials (Noth et al 1984;Töpper et al 1993) and deficits in feedback control when external perturbations are introduced during reaching movements (Smith et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The basal ganglia (BG) are an important part of a complex neural network that processes and integrates various sensory inputs in order to produce and modulate motor outputs (Contreras-Vidal, 1999;Graziano & Gross, 1993;Houk & Wise, 1995;Nagy, Eordegh, Paroczy, Markus, & Benedek, 2006). Boecker and colleagues termed the BG a "sensory analyzer" engaged in central somatosensory control, suggesting interconnections between the cortex, BG and thalamus that make up an indirect BG-sensory loop (Boecker et al, 1999b). In Parkinson's disease (PD) there is a degeneration of dopaminergic neurons in the BG, specifically in the substantia nigra pars compacta, which impairs the basal ganglia-cortical circuitry.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Studies have shown that individuals with PD have abnormal processing of sensory information, specifically proprioceptive inputs (Klockgether et al, 1995;Rickards & Cody, 1997;Schneider et al, 1987;Zia et al, 2000). Abnormal vibration-induced movement errors have been observed in PD during joint flexion-extension tasks (Rickards & Cody, 1997;Schrader et al, 2008), and PET imaging studies of passive finger vibration have demonstrated a reduction in sensory evoked brain activations in the cortical (parietal and frontal) and subcortical (BG) areas of the brain (Boecker et al, 1999a). During limb position tasks, individuals with PD make more errors then healthy control participants when required to identify the occurrence and/or direction of passive movements (Schneider et al, 1987) as well as demonstrating greater errors in matching static limb position, detecting limb displacements, or using the lower limbs to estimate the size of an object (Martens & Almeida, 2011;O'Suilleabhain, Bullard, & Dewey, 2001;Zia et al, 2000).…”
Section: List Of Tablesmentioning
confidence: 99%